Frequency of use and sonority sequencing in first- and second-language consonant cluster perception: facilitation is language-specific - Wulfert, Sophia; Auer, Peter; Hanulíková, Adriana (Frontiers in Psychology, 2025)
IntroductionExpectations derived from knowledge about the likelihood of different phoneme sequences are an effective cognitive mechanism to make the listening process more efficient. In addition to language-specific distributions, universal principles of well-formedness may play a role, especially in second language listening, where the listeners are less familiar with the target language. In our study, we compared two listener groups to investigate the relative influences of consonant cluster frequency and consonant sequencing in accordance with the Sonority Sequencing Principle on the perception of initial consonant clusters in German.MethodsIn Experiment 1, first-language (L1) German listeners identified noise-embedded nonce words with initial consonant clusters. In Experiment 2, Australian learners of German completed the same task.ResultsGerman consonant cluster frequency had a significant facilitating influence on perception accuracy for both groups, which was even more pronounced for the L2 listeners. Conformity with the Sonority Sequencing Principle, on the other hand, had a significant inhibitory effect for both listener groups, contrary to expectations.DiscussionThis suggests that it is experience with language-specific distributions that guides sublexical speech processing, also in an L2, while sonority sequencing does not play a facilitative role but rather seems to be correlated with a factor inhibiting successful recognition.